Multiple patho-phenotyping and molecular analysis to characterize wide-spectrum durable leaf rust resistance in wheat collections from India - Mohan, Ram; Singh, Vaibhav Kumar; Chetan, K. K.; Rani, Lingareddy Usha; Sameriya, Koshal K.; Kumar, Subodh; Bainsla, Naresh Kumar; Senthilraja, Govindasamy; Saharan, Mahender Singh (Frontiers in Microbiology, 2025)
Wheat leaf rust, caused by Puccinia triticina (Pt), is a globally prevalent fungal disease that causes significant economic loss. Cultivar resistance remains a cornerstone of the management of this pathogen. This study evaluated 86 Indian wheat (Triticum aestivum L.) genotypes to characterize leaf rust resistance (Lr) genes, assess adult plant resistance (APR) under field conditions, and validate resistance using molecular marker analysis. Seedling resistance tests against 14 Pt pathotypes identified nine key Lr genes (Lr1, Lr3, Lr10, Lr14a, Lr16, Lr23, Lr24, Lr26, and Lr34) in 26 genotypes, either alone or in combination with other resistance genes. Field evaluations across two consecutive rabi seasons (2020–21 and 2021–22) revealed quantitative, partial, non-race-specific, slow-rusting APR in over 64 genotypes. These genotypes, which are susceptible to prevalent Pt pathotypes at the seedling stage, demonstrated that APR is mediated by minor-effect genes. Epidemiological parameters (final disease severity, coefficient of infection, relative area under the disease progression curve, and infection rate) showed strong positive correlations, validating their utility for quantifying slow-rusting resistance. Molecular analysis detected Lr34 in 33 genotypes, followed by Lr10 (24 genotypes), and Lr24 (16 genotypes), confirming their role in conferring resistance. Genotypes that combine seedling and APR resistance, particularly those harboring Lr34, Lr10, or Lr24, offer valuable genetic resources for breeding programs. Their integration into wheat improvement initiatives can enhance resistance against evolving Pt pathotypes, mitigate yield losses, and contribute to sustainable wheat production. This study underscores the importance of deploying multigenic resistance strategies to counter rapid pathogen evolution and ensure long-term disease management.